Early Blight Disease Management of Tomato through Use of Native Bioresources in Mid Hills of Himachal Pradesh - Attri, Kaushal; Gupta, Pankaj; Kansal, Sandeep; Gupta, Meenu; Goswami, Manika (International Journal of Bio-resource and Stress Management, 2020)
Early blight of tomato also known as target leaf spot disease caused by Alternaria solani (Ellis and Martin) Jones and Grout is important disease of tomato. To manage the disease, six plant origin pesticides and cow urine based bioresource were assessed under in vitro and field conditions. The results of present investigations revealed that cow urine and Roylea elegans (kadu) showed cent per cent mycelial growth inhibition followed by Justicia adhatoda, Vitex negundo and Allium sativum which resulted in 88.15, 84.44 and 80.00% growth inhibition at 15% concentration. To study the effect of these bioresources under field conditions five foliar sprays were given at ten days interval after commencement of disease. It was revealed that foliar application of bioresources, significantly reduced the disease severity and increased the yield. Five foliar sprays of Allium satium (garlic) at ten days interval was found most effective in decreasing the severity of disease to 56.12% followed by Justicia adhatoda (basunti), Melia azedarach (darek) and cow urine which resulted in 44.24, 38.71 and 37.92% reduction of disease respectively, whereas, leaf water extract of Vitex negundo (banah) was least significantly effective and resulted in 28.50% reduction of disease. Five successive sprays of Allium sativum (garlic) also resulted in maximum yield of fruits (18.40 kg plot-1) followed by Justicia adhatoda (basunti) (13.52 kg plot-1), cow urine (13.00 kg plot-1) and Nerium indicum (12.70 kg plot-1)